The role of self-efficacy in mediating the influence of social support on academic resilience among college students - Kelly, Estalita; Murwani, Fulgentius Danardana; Hitipeuw, Imanuel; Eva, Nur (Association for Scientific Computing Electrical and Engineering(ASCEE), 2025)
Academic resilience is an increasingly relevant issue in the digital age, particularly as students face mounting academic demands alongside rapid technological advancement. Students who struggle to adapt to new technologies often experience heightened stress and reduced academic performance. This study investigates the mediating role of self-efficacy in the relationship between social support and academic resilience among university students. Employing a correlational causal design, the study surveyed 424 students from Pasuruan, East Java, selected through stratified random sampling. Data were collected using validated scales measuring perceived social support, self-efficacy, and academic resilience. Path analysis, supported by SPSS 22.0, revealed that self-efficacy significantly mediates the effect of social support on academic resilience (Sobel Z = 13.491, p 0.01). The indirect effect of social support through self-efficacy (Î² = 0.569) was notably stronger than the direct effect (Î² = 0.082), indicating that students' belief in their own abilities plays a more critical role in fostering resilience than external support alone. In essence, students with low self-efficacy may perceive themselves as incapable of overcoming academic challenges, even when supported by others. Conversely, those with high self-efficacy remain confident and persistent, even in the face of limited social support. These findings underscore the importance of strengthening both internal psychological resources and external support systems to enhance student resilience. Institutions should prioritize integrated interventions, combining peer support, counseling, and self-efficacy development, to foster adaptive coping mechanisms and long-term academic success.